Self-assembled epitope-based nanoparticles targeting the SARS-CoV-2 spike protein enhanced the immune response and induced potential broad neutralizing activity - Liu, Yue; Li, Chenxi; Wu, Zirui; Zhao, Yu; Yin, Tieyan; Liu, Xiaopan; Hui, Jiaru; Wang, Qingyu; Pan, Yi; Shan, Yaming; Qu, Xinglong (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe ongoing COVID-19 has caused a global pandemic, resulting in millions of infections and deaths. While current vaccines target the SARS-CoV-2 spike (S) protein, its high mutation rate significantly compromises vaccine efficacy. We aimed to evaluate the potential of epitope-based nanoparticles (NPs) to induce broad cross-protection and durable immune responses against SARS-CoV-2.MethodsFour conserved epitopes derived from the receptor-binding domain (RBD) and S2 subunit of the spike protein were integrated into Helicobacter pylori ferritin to create epitope-based NPs named S18-F, RBM-F, UH-F, and HR2-F. The immunogenicity of the epitope-based NPs was evaluated through animal experiments to measure epitope-specific antibody titers and assess neutralizing activity against SARS-CoV-2 pseudovirus. To characterize cellular immune responses, splenic lymphocyte proliferation following epitope stimulation was measured, and cytokine secretion profiles including IFN-γ, IL-2, IL-4, and IL-10 were analyzed to determine Th1/Th2 immune polarization. Antibody-dependent cellular cytotoxicity (ADCC) assays were performed to evaluate NP-enhanced recognition and elimination of infected target cells.ResultsThese NPs induced high titers of epitope-specific antibodies lasting three months post-immunization. Sera from the RBM-F, UH-F, and HR2-F groups exhibited neutralizing activity against the SARS-CoV-2 pseudovirus WH-1 in vitro. Splenic lymphocytes from the S18-F, RBM-F, and UH-F groups showed significantly increased proliferation. Lymphocytes from the RBM-F group demonstrated increased secretion of IFN-γ, IL-2, IL-4, and IL-10 cytokines, indicating a balanced Th1 and Th2 immune response. Immune sera from the S18-F and mixed-immunized groups exhibited antibody-dependent cellular cytotoxicity.DiscussionThe results indicate that these NPs induce robust humoral and cellular immune responses, potentially offering a promising strategy for effective vaccine development against SARS-CoV-2.